High, Middle or Low? Acts of an International Colloquium on Absolute Chronology Held at the University of Gothenburg, 20th-22nd August 1987. Part 1 and Part 2 (1987)
Beitrag G. Wilhelm - J. Boese, Part 1, 74-117 bereits 49:1941